2007
DOI: 10.1002/ajim.20462
|View full text |Cite
|
Sign up to set email alerts
|

Job categories and acute ischemic heart disease: a hospital‐based, case‐control study in Taiwan

Abstract: Blue-collar workers had a 5.3-fold increased risk of a first event of non-fatal acute IHD compared with white-collar workers, and this increased risk was associated with a clustering of cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Netterstrom et al 2006 High job demands contributed significantly to IHD incidence. Chen et al 2007 Blue collar workers had a 5.3-fold (95% CI 1.5 to 18.5) increased risk of acute IHD. a Statistically significant; b nr, not related to CVD risk.…”
Section: Netterstrom Et Al 1999mentioning
confidence: 98%
“…Netterstrom et al 2006 High job demands contributed significantly to IHD incidence. Chen et al 2007 Blue collar workers had a 5.3-fold (95% CI 1.5 to 18.5) increased risk of acute IHD. a Statistically significant; b nr, not related to CVD risk.…”
Section: Netterstrom Et Al 1999mentioning
confidence: 98%
“…Studies from Europe and the USA found that blue‐collar workers had three‐times the risk of cardiovascular disease (CVD; Netterstrom, Nielsen, Kristensen, Bach, & Moller, 1999) and ischemic heart disease (Chen, Cheng, Lin, & Hsiao, 2007; Netterstrom, Kristensen, & Sjol, 2006; Tuchsen & Endahl, 1999) compared with white‐collar workers. These studies provide evidence that workers from more disadvantaged groups and lower socioeconomic classes are at higher risk of CVD (Hwang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the type of occupation, it has been associated with CVD development, with blue-collar workers or low-level employees having increased mortality [32,33], as well as higher likelihood for a coronary [34,35] or a stroke event [36]. As far as blue-collar workers are concerned, they generally have to cope with higher occupational stress and may turn to unhealthier behaviors, such as smoking, as a means for anxiety reduction [37].…”
Section: Discussionmentioning
confidence: 98%